Classifying 3-D Models of Coral Reefs Using Structure-From-Motion and Multi-View Semantic Segmentation - Jordan Pierce; Mark J. Butler; Yuri Rzhanov; Kim Lowell; Jennifer A. Dijkstra (Frontiers in Marine Science, 2021)
Benthic quadrat surveys using 2-D images are one of the most common methods of quantifying the composition of coral reef communities, but they and other methods fail to assess changes in species composition as a 3-dimensional system, arguably one of the most important attributes in foundational systems. Structure-from-motion (SfM) algorithms that utilize images collected from various viewpoints to form an accurate 3-D model have become more common among ecologists in recent years. However, there exist few efficient methods that can classify portions of the 3-D model to specific ecological functional groups. This lack of granularity makes it more difficult to identify the class category responsible for changes in the structure of coral reef communities. We present a novel method that can efficiently provide semantic labels of functional groups to 3-D reconstructed models created from commonly used SfM software (i.e., Agisoft Metashape) using fully convolutional networks (FCNs). Unlike other methods, ours involves creating dense labels for each of the images used in the 3-D reconstruction and then reusing the projection matrices created during the SfM process to project semantic labels onto either the point cloud or mesh to create fully classified versions. When quantitatively validating the classification results we found that this method is capable of accurately projecting semantic labels from image-space to model-space with scores as high as 91% pixel accuracy. Furthermore, because each image only needs to be provided with a single set of dense labels this method scales linearly making it useful for large areas or high resolution-models. Although SfM has become widely adopted by ecologists, deep learning presents a steep learning curve for many. To ensure repeatability and ease-of-use, we provide a comprehensive workflow with detailed instructions and open-sourced the programming code to assist others in replicating our methodology. Our method will allow researchers to assess precise changes in 3-D community composition of reef habitats in an entirely novel way, providing more insight into changes in ecological paradigms, such as those that occur during coral-algae shifts.